A Method for Assessing the State of the Snow and Ice Cover by the Brewster Angle - V. G. Mashkov; V. A. Malyshev; P. A. Fedyunin (Известия высших учебных заведений России: Радиоэлектроника, 2021)
Introduction. Landing is the most challenging and dangerous part of the helicopter flight. The development of systems facilitating safe landing is a priority task for both Russian and foreign engineering companies. Landing on unprepared sites covered with snow and ice may be determined by the need to deliver cargo and ammunition in combat conditions, during search and rescue operations, evacuations of victims, etc.Aim. Development of a method for remote assessment of the snow and ice cover based on the results of oblique sensing of the underlying surface with a radio signal with vertical polarization.Materials and methods. In the MatLab environment, the authors conducted numerical simulations of Fresnel reflection coefficients of echo signals with vertical polarization in the 40–90 degree sensing range in the operating frequency range when solving the direct and inverse problem of reconstruction of the parameters of snow and ice layers.Results. Intervals of the Brewster angle values were obtained at which the value of the Fresnel reflection coefficient from the boundaries of the snow and ice cover takes minimal. Thus, was found to be – 47...55°, – 55...58° and – 58...61° for dry snow, dry firn and dry ice, respectively. The depth resolution when using an ultra-wideband LFM signal with a frequency from 2 to 8 GHz is about 4 cm. The methodological error in determining the dielectric permittivity of layers by the Brewster angle comprises not more than 3 %.Conclusion. The error in determining the relative permittivity and the depth of k layers under an increase in the RMS values of the noise level from 3.8 to 4.8 with a step of 0.1 for 100 implementations of each with a probability of 0.95 does not exceed 10 %, which confirms the validity of this method. The implementation of which allows you to automate the process of evaluating the possibility of a safe landing, thereby reducing the decision-making time and increasing the level of safety.